Implementasi Sistem Penjamin Mutu Pendidikan (SPMP) dalam Rangka Meningkatkan Mutu Sekolah - AM, Sudrajat (Journal of Islamic Education Counseling, 2022)
The Education Quality Assurance System is the entire function of education management that develops the duties and responsibilities in measuring and assessing the fulfillment of quality standards. SMK IT Miftahul Huda is one of the schools that has implemented the Primary and Secondary Education Quality Assurance System, which is in accordance with the established indicators, namely the Eight National Education Standards.